2013
DOI: 10.1371/journal.pone.0066260
|View full text |Cite
|
Sign up to set email alerts
|

The RhoGEF TEM4 Regulates Endothelial Cell Migration by Suppressing Actomyosin Contractility

Abstract: Persistent cellular migration requires efficient protrusion of the front of the cell, the leading edge where the actin cytoskeleton and cell-substrate adhesions undergo constant rearrangement. Rho family GTPases are essential regulators of the actin cytoskeleton and cell adhesion dynamics. Here, we examined the role of the RhoGEF TEM4, an activator of Rho family GTPases, in regulating cellular migration of endothelial cells. We found that TEM4 promotes the persistence of cellular migration by regulating the ar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
28
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(32 citation statements)
references
References 76 publications
(101 reference statements)
4
28
0
Order By: Relevance
“…TEM4 upregulation was identified in the endothelial cells during tumor angiogenesis of colorectal cancer patients [39]. Consistent with the TEM4 central role in controlling activation of RhoC in endothelial cells, the organization of actin cytoskeleton, cell-substrate adhesion, and cellular migration, it is suggested that TEM4 is critical for blood vessel formation during angiogenesis [105]. …”
Section: Tumor Endothelial Markers (Tems)mentioning
confidence: 85%
See 1 more Smart Citation
“…TEM4 upregulation was identified in the endothelial cells during tumor angiogenesis of colorectal cancer patients [39]. Consistent with the TEM4 central role in controlling activation of RhoC in endothelial cells, the organization of actin cytoskeleton, cell-substrate adhesion, and cellular migration, it is suggested that TEM4 is critical for blood vessel formation during angiogenesis [105]. …”
Section: Tumor Endothelial Markers (Tems)mentioning
confidence: 85%
“…TEM4 is localized in the subcellular compartment. The biological role of TEM4 is associated with regulating activation of Rho GTPases, various members of the cadherin-catenin complex, and several cytoskeleton proteins [105, 106]. TEM4 upregulation was identified in the endothelial cells during tumor angiogenesis of colorectal cancer patients [39].…”
Section: Tumor Endothelial Markers (Tems)mentioning
confidence: 99%
“…In endothelial cells, TEM4 appears critical for organization of the actin cytoskeleton and integrin-based adhesions at membrane protrusions of migrating cells 180 . This work was followed up by Ngok and co-workers, who showed that TEM4 associates with the cadherin complex at endothelial cell–cell junctions in confluent monolayers, independent of F-actin binding, whereas TEM4 remains associated with the F-actin cytoskeleton in cells cultured at low density 181 .…”
Section: Introductionmentioning
confidence: 94%
“…For example, Wang and colleagues have observed that RhoC knockdown decreases migration and invasion of human mammary endothelial cells (Wang et al, 2008), whereas our results suggest that RhoC knockdown increases HUVEC migration. Previous HUVEC studies have demonstrated that RhoC deletion promotes vascular sprouting twofold (Del Galdo et al, 2013), and that RhoC knockdown results in a loss-of-directionality migration phenotype and inefficient migration from the point of origin in single-cell tracking experiments (Mitin et al, 2013). The discrepancy in HUVEC migration might stem from the different assays utilized and inherent differences in the migratory properties of a single cell versus numerous cells.…”
Section: Discussionmentioning
confidence: 99%